Changes in Anterior, Posterior, and Total Corneal Astigmatism after Descemet Membrane Endothelial Keratoplasty. (2nd May 2017) - Alnawaiseh, Maged; Zumhagen, Lars; Rosentreter, André; Eter, Nicole
Abstract : Purpose . To evaluate changes in anterior, posterior, and total corneal astigmatism in patients after Descemet membrane endothelial keratoplasty (DMEK). Methods . We retrospectively included 29 eyes of 23 patients (age 67.6 ± 9.8 years, 13 female, 10 male) after DMEK surgery. The magnitude and axis orientation of anterior, posterior, and total corneal astigmatism before and after DMEK were determined using a rotating Scheimpflug system (Pentacam HR, Oculus). Results . The magnitude of anterior, posterior, and total corneal astigmatism in the central cornea did not change significantly after surgery. Before surgery, we found a significant correlation between the magnitudes of anterior and posterior corneal astigmatism (Spearman's correlation coefficient r S = 0.526, P = 0.003 ), while after surgery this correlation was no longer significant (r S = 0.038, P = 0.843 ). There was a significant correlation between the vector difference between preoperative and postoperative posterior astigmatism and the change in corneal pachymetry (r P = 0.47, P = 0.010 ). Conclusions . Posterior corneal astigmatism (especially the orientation) and therefore the relationship between anterior and total corneal astigmatism may change after DMEK. This should be considered to improve the accuracy of toric IOL power calculations following phakic DMEK or in combined procedures.